Analisis Perilaku Penyimpangan Sosial Remaja Gay Di Era Digital - Nonik Fatimatuz Zahroh; Ida Fina; Herin Ratna Rahmadhanik; Dzalika Ananda Suhariyoso (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The fast development of information technology, especially in handheld communication devices (smartphones) is undeniable that it is difficult to avoid massively by the public. Its existence will be a tool of personal reconstruction in society. Not only as a means of communication, but far beyond the basic functions of smartphones. The important role of technology is what brings human civilisation into the digital era. The digital era has brought various good changes as a positive impact that can be used as well as possible. Through a smartphone, users can show their activities and build their social identity, both in the real and virtual world. Deviant sexual orientation makes it difficult for gays to interact and communicate like a dominant society, it makes gays need an alternative media in order to interact and communicate with the aim of meeting their social and sexual needs. The result of this discussion is that in the digital era it is no longer a taboo for most teenagers to find out information about the whereabouts of gay men. Gay youth communication on social media is divided into two types, namely verbal and non-verbal. The existence of verbal and non-verbal communication in social media can support the realisation of meetings in real life.